1993
DOI: 10.1515/cclm.1993.31.7.433
|View full text |Cite
|
Sign up to set email alerts
|

A New Look at the Limits of Detection (LD), Quantification (LQ) and Power of Definition (PD)

Abstract: The relationship between the concentration of the analyte and the imprecision of an analytical method can be displayed by the precision profile in which the coefficient of variation (relative standard deviation) is plotted against the concentration of the analyte. The function of the curve of the profile and its confidence limits can easily be assessed by a computer program developed by W. A. Sadler & M. H. Smith (Clin. Chem. 36 (1990), 1346 -1350. For the assessment of limits of detection and of quantificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
2

Year Published

1994
1994
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 13 publications
0
18
0
2
Order By: Relevance
“…Further publications have shown that this observation is also valid for other procedures (3). At each analyte concentration a specific imprecision must therefore be expected and general data cannot be given.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Further publications have shown that this observation is also valid for other procedures (3). At each analyte concentration a specific imprecision must therefore be expected and general data cannot be given.…”
Section: Introductionmentioning
confidence: 89%
“…The calculation of the precision profile, the lower limit of quantification (LLQ), the limit of detection (LD) and the power of definition (PD) has been described previously (3). In short: the precision profile (CV versus analyte concentration) can be derived from the varianee function.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 " 13 Using the computer program by Sadler and Smith, 14 the variance was calculated for each triplicate measurement and the variance profile was constructed out of the individual variances. The parameters of the variance function were defined by an iterative procedure.…”
Section: Methodsmentioning
confidence: 99%
“…10 By setting the platelet number to "zero" in the variance function, the ]. This standard deviation was used to construct a normal distribution representing the random error of the blank (ie, the background noise of the instrumental system).…”
Section: Methodsmentioning
confidence: 99%